Makroavertebrata Bentos sebagai Bioindikator Kualitas Air Sungai Nimbai Manokwari, Papua Barat - Simon Petrus Oktovianus Leatemia; Emmanuel Manangkalangi; Paskalina Theresia Lefaan; Hans Fence Zakeus Peday; Luky Sembel (Jurnal Ilmu Pertanian Indonesia, 2017)
Benthos macroinvertebrates have been used as bioindicators to assess the waters quality of the stream, but still are very rarely to applied in West Papua streams. Benthos macroinvertebrates can describe the stream water quality so that very well be used as bioindicators, due to each species has a different tolerance to interference organic pollutants in waters. This study aimed to assess the water quality of Nimbai stream using benthos macroinvertebrates tolerance level and several water quality parameters. Data retrieval was conducted in JuneJuly and SeptemberOctober 2012 in seven stations (L1L7) from Nimbai upstream to downstream that connected to Prafi river. The water macroinvertebrates were taken using surber with mesh size 200 μm and then was identified at the family level. At L5 station near the oil palm waste disposal installations was contains oil and fat (<1-3 mg/l), which resulted in dissolved oxygen (DO) and pH is lower than the other stations. Similarly the value of H' is low (0.83), however, the value of C (0.79) was high that dominated by Oligochaeta. Famili biotic index (FBI) value obtained showed that water quality in the L1L4 stations was in good to excellent condition, but the quality at L5 station is classified as very poor. As the distance far away from the sources of pollution in the L5 station, water quality tends to improve as shown in the L6 and L7 stations. The result of this study shows the important benefits of benthos macroinvertebrates as bioindicators for assessing the quality of stream waters, and can be described aquatic environments disturbance to the benthos macroinvertebrates habitats in Nimbai stream.